Evaluasi terhadap Program Agropolitan di Jawa Tengah - Handayani, Alfina; Jamal, Rachman; Komalawati; Kristanto, Budi Adi (Jurnal Bina Praja, 2021)
Agropolitan has been considered a solution for minimizing urbanization and creating equitable development between rural and urban areas. It has been one of the programs mentioned in the spatial planning agendas of the Government of Central Java. In Central Java, agropolitan has been started in 2002 and has left many problems related to the implementation. The objective of this study is to evaluate the implementation of agropolitan in Central Java. The research was conducted from April to October 2019. This study uses purposive sampling in determining the sample of the performance of the agribusiness sub-terminal at that location. The research started by completing pre-surveys to gain a brief description of the study areas and agropolitan program. The research collected in-depth information about the agropolitan program through focus group discussions and in-depth interviews with farmer respondents, traders, and ofï¬cers involved in agropolitan activities. Data were analyzed using scoring factors and descriptive qualitative. The results showed that in terms of projects, the implementation of agropolitan activities was in a GOOD category, but it was in the MEDIUM category in terms of sustainability. Furthermore, lack of community involvement, support from local government, the unavailability of an exit strategy, and the inflexibility of STAs to sell different commodities were some problems encountered in the implementation and sustainability of the program. As agropolitan is still one of the priorities of the Central Java Government, it is recommended to involve all stakeholders in the whole stages of the program from planning to evaluation, optimize or reactivate the Agropolitan working group, develop an institution that could sustainably implement the programs and the facilities, as well as increase human resource capacity.